Implications of Fintech Developments for Traditional Banks - Chen, Kuan-Chieh (International Journal of Economics and Financial Issues, 2020)
As financial technology has developed, the Chinese government has deregulated banks. The first Internet-only bank was established in 2014, but the effects of Internet-only banking on traditional banks remain unclear. However, we discussed two stages (2009-2014; 2015-2018), namely before and after the entry of Internet-only banking into the financial market. Data envelopment analysis and regression methods were used to evaluate efficiency and performance and observe changes between banks in different periods, of 20 banks. The highlights of our findings are as follows: First, overall bank efficiency has improved since Internet-only banking entered the financial market. Second, in the era of low-interest spreads, banks are diversifying operational income while improving performance and efficiency. Furthermore, with the development of FinTech and competitive pressure, banks should downsize to strengthen their competitiveness and improve their internal environments. Finally, operating income generated by employees has increased, but profits have decreased, implying that employees are highly skilled and efficient. Thus, banks may be required to offer higher salaries, which reduce profits. Keywords: Internet-only bank, Network DEA, Bank efficiency, Bank performance JEL Classifications: G19, G20, G29 DOI: https://doi.org/10.32479/ijefi.10076